A feasibility study of a RFID traceability system in municipal solid waste management. (1st January 2013) - Gnoni, Maria Grazia; Lettera, Gianni; Rollo, Alessandra
Radio frequency identification (RFID) is currently an interesting enabling technology applied in several contexts for tracing items and people starting from logistics to healthcare management. An effective tracing system could improve heavily performances of an integrated municipal solid waste management systems. Focusing on waste collection services, one key point is to trace wastes (in their quantity and typology) collected from citizens in order to apply more transparent fee mechanisms, i.e., based on 'pay-as-you-through' principle. The present paper proposes a feasibility study about the application of RFID technology for tracing actual wastes intercepted by collection services in municipal solid waste management system. After the proposed model design, a simulation analysis has been carried out to assess actual impacts (positive or negative) on waste collection procedures due to the introduction of this technology. Finally, different organisational scenarios for collection services based on RFID application have been compared in terms of both technical and economic indicators.